2019
DOI: 10.25259/sni-88-2019
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic accuracy and frame mounting: A phantom study

Abstract: Background: Frame mounting is considered one of the most critical steps in stereotactic neurosurgery. In routine clinical practice, the aim is to mount the frame as symmetrical as possible, parallel to Reid’s line. However, sometimes, the frame is mounted asymmetrically often due to patient-related reasons. Methods: In this study, we addressed the question whether an asymmetrically mounted frame influences the accuracy of stereotactic electrode implantation. A Citrullus lanatus was used for this study. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…It is therefore difficult to determine whether we are looking at a systemic error in the experimental setup or not, an explanation is yet to be found. Previous studies have addressed inaccuracies in frame-based stereotactic procedures due to asymmetrical mounting or distortions of the stereotactic device (Treuer et al, 2004 ; Alptekin et al, 2019 ; Renier and Massager, 2019 ). In the present phantom study, only the manual attachment of the stereotactic arc and the trajectory adjustment differed from the robotic procedure, not the positioning of the frame.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore difficult to determine whether we are looking at a systemic error in the experimental setup or not, an explanation is yet to be found. Previous studies have addressed inaccuracies in frame-based stereotactic procedures due to asymmetrical mounting or distortions of the stereotactic device (Treuer et al, 2004 ; Alptekin et al, 2019 ; Renier and Massager, 2019 ). In the present phantom study, only the manual attachment of the stereotactic arc and the trajectory adjustment differed from the robotic procedure, not the positioning of the frame.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to awake procedures, the patient is able to sit up with the head straight, ensuring speedy and accurate mounting of the device. While the mounting may be reported to be painful and uncomfortable, it has to be carried out with special attention as the SF must be positioned as symmetrical as possible and parallel to Reid’s baseline [ 3 ]. In the case of awake DBS, pain and discomfort may be experienced by patients suffering from Parkinson’s disease (PD) during SF fixation as well as during scalp incision and may compromise their adherence to the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors focus on the difference between the intended-totarget point and the observed location of the contacts and calculate an "error of targeting" (Li et al, 2016), yet doing so they skip the deformation of the electrode and hide the different causes of the mismatch. However, although reductive, it emphasizes the notion of surgical inaccuracy, which is true for several reasons: (1) current stereotactic frames (surgical instrument for the implantation of the electrodes) and robotized systems have an intrinsic mean geometrical error usually of 1 mm (von Langsdorff et al, 2015;Alptekin et al, 2019); (2) manual measurements on X-ray films and surgical software introduce errors or inaccuracy, such as the difficulties of reading stereotactic rules (visual interpolation) and contact position on X-rays; (3) manipulation of surgical tools introduces limitations to the leaving and securing of electrodes in place (Contarino et al, 2013), with a global (2 + 3) precision roughly estimated, at around 1 mm; (4) erroneous targeting should be exceptional (pure error of targeting); and (5) mechanical issues can be encountered during the progression of the electrode, such as friction at the dura aperture, deviation by a foreign body along the tract such as surgical wax used for bone hemostasis, presence of significant blood vessels and arachnoid adherences, and changing of medium from tissue to ventricle and conversely. This notion of surgical inaccuracy should be separate from the delayed lead migration explained by mechanical issues such as technical error, repetitive dystonic head movement, and Twiddler's syndrome and reported between two CT scans separated by a mean interval of 1 year (differences of tip position or length of electrode > 3 mm) (Morishita et al, 2017).…”
Section: Introductionmentioning
confidence: 99%